Analysis of Images of Neutrophil Lymphocyte Ratio and Bacteria Density Level of Helicobacter Pylori in Tissue in Gastritis Patients - Fadia Rakhmalia; Anik Handayati; Evy Diah Woelansari; Mohd Nazil Salleh (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Gastritis is an inflammatory disease that can last for a long time. Helicobacter pylori infection is known as the main cause of peptic ulcer and the most common cause of gastritis. Helicobacter Pylori infection will cause mononuclear (MN) and polymorphonuclear (PMN) cell infiltration and will increase the production of proinflammatory cytokines in the gastric mucosa compared to non-Helicobacter Pylori gastritis. Helicobacter Pylori with histopathological examination diagnosis. This type of research is descriptive observational with purposive sampling data collection technique at the Anatomical Pathology Laboratory Installation, RSPAL dr. Ramelan Surabaya. The data used are the results of a biopsy of 60 samples that were determined as gastritis with histopathological examination of the identification of Helicobacter Pylori bacteria in gastric tissue classified by the level of bacterial density using The Updated Sydney System, as well as haemogram data for complete blood examination to further calculate the neutrophil lymphocyte ratio (NLR). The data were processed using descriptive statistical tests to determine the average neutrophil lymphocyte ratio (NLR). Based on the statistics of the r-Spearman test, the density of Helicobacter Pylori, (Pν = 0.000) below < 0.005 indicates that there is a strong relationship between the neutrophil lymphocyte ratio (NLR) and the density of Helicobacter Pylori bacteria.